Picnic - Burningham, John. (Somerville, Mass. : Candlewick Press, 2014)
Boy and Girl go out for a picnic and meet all sorts of animals along the way.
Originally published: London: Jonathan Cape, 2013.
Booklist starred
Publisher's Weekly
School Library Journal
Booklist starred, April 2014
Publisher's Weekly, March 2014
Keywords: Friendship -- Juvenile fiction; Picnics -- Juvenile fiction; Friendship -- Fiction; Picnics -- Fiction; Friendship -- Fiction; Picnics -- Fiction; Picture books for children